Weak Convergence Theorems for Mixed Type Total Asymptotically Nonexpansive Mappings in Uniformly Convex Banach Spaces (Journal of Mathematical Study, 2021)
In this paper, we study a new two-step iteration scheme of mixed type fortwo total asymptotically nonexpansive self mappings and two total asymptoticallynonexpansive non-self mappings and establish some weak convergence theorems inthe framework of uniformly convex Banach spaces. Our results extend and generalizeseveral results from the current existing literature.
Keywords: Total asymptotically nonexpansive self and non-self mapping; mixed type iteration scheme; common fixed point; uniformly convex Banach space; weak convergence.